2018
DOI: 10.3389/fimmu.2018.00366
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Replication of Virulent Newcastle Disease Virus in Chicken Macrophages Is due to Polarized Activation of Cells by Inhibition of TLR7

Abstract: Newcastle disease (ND), caused by infections with virulent strains of Newcastle disease virus (NDV), is one of the most important infectious disease affecting wild, peridomestic, and domestic birds worldwide. Vaccines constructed from live, low-virulence (lentogenic) viruses are the most accepted prevention and control strategies for combating ND in poultry across the globe. Avian macrophages are one of the first cell lines of defense against microbial infection, responding to signals in the microenvironment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Thereafter, cells were absorbed with virus at 100 μl allantoic fluid containing the Hubei isolate for 1 hr in the presence or absence of TPCK‐trypsin (Sigma, Shanghai, China) and fresh medium was added into the well and then incubated with 72 hr post infection (hpi). Subsequent to infection, virus titre in the supernatants was measured using a micro‐hemagglutination assay (HA) method (Zhang et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, cells were absorbed with virus at 100 μl allantoic fluid containing the Hubei isolate for 1 hr in the presence or absence of TPCK‐trypsin (Sigma, Shanghai, China) and fresh medium was added into the well and then incubated with 72 hr post infection (hpi). Subsequent to infection, virus titre in the supernatants was measured using a micro‐hemagglutination assay (HA) method (Zhang et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the levels of IFN-β, IFN-γ, IL-1β and IL-4 in peripheral blood mononuclear cells of broilers were significantly up-regulated after TLR7 agonist Resiquimod was used [54]. It has also been found that the highly virulent NDV strain can block the expression of TLR7 in chicken macrophages and enhance replication [55]. In this study, interference of TLR7 down-regulated two kinds of interleukins, suggesting that TLR7 may be involved in the defense against viruses by promoting the expression of immune factors in broilers.…”
Section: Plos Onementioning
confidence: 99%
“…For poultry vaccines, a good candidate for such assays is the chicken macrophage-like cell line HD11, which shows broad expression of PRRs, including toll-like receptors (TLRs) [ 16 ]. The HD11 cell line has already been employed to explore the immune-activating or immunomodulatory properties of TLR agonists [ 17 , 18 , 19 ], liposomes [ 20 ], host defense peptides [ 21 ], cytokines [ 22 , 23 , 24 ], bacteria [ 17 , 21 , 25 ], and replicating viruses [ 26 , 27 , 28 ], using nitric oxide production as a functional readout of macrophage activation. Macrophages produce nitric oxide using the enzyme-inducible nitric oxide synthase (iNOS), which is expressed upon stimulation of PRRs and downstream activation of transcription factor nuclear factor kappa B (NF-κB) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%